HATE SPEECH ACTS: A CASE IN BATU BARA - Rahmadsyah Rangkuti; Andi Pratama; Zulfan Zulfan (Universitas Islam Sumatera Utara (UISU), 2019)
Hate speech acts that occur in the online realm expressed with words of prejudice and negative feelings are far more dangerous than in the offline realm. Hate speech is a new area in the study of illocutionary speech acts. This new area of speech acts becomes more interesting because every hate speech has various meanings or illocutionary forces based on speaker’s intention. This study aims to analyse the classifications and aims of illocutionary acts and illocutionary forces of hate speech contained in two face book group accounts related to Batu Bara district’s local election. The research method is descriptive qualitative. The data of this research are thirteen utterances/speeches of face book users in Batu Bara district’s local election group account. Data were collected using the documentation method with the help of referring technique. This method is used to observe the expression of the face book users’ hatred on issues related to social, cultural and political background on each candidate. Thirteen utterances analyzed are classified into assertive, directive and expressive and have illocutionary forces namely insulting, inciting and discriminating. This study indicates that hate speech can be identified linguistically.